1995
DOI: 10.1099/00222615-42-1-43
|View full text |Cite
|
Sign up to set email alerts
|

No difference in enterotoxin production among Staphylococcus aureus strains isolated from blood compared with strains isolated from healthy carriers

Abstract: The production of enterotoxin A, B, C and D by 196 Staphylococcus aureus strains isolated from blood cultures and 95 strains from nasal carriers was investigated. Half of the bacteraemia strains were from patients who died with or because of their infection, the other half from patients who survived. The nasal strains were selected to match the bacteraemia strains regarding phage types. Overall, 30.6% of the bacteraemia strains and 40.0% of the nasal strains produced enterotoxins; enterotoxins B and C were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
3

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 7 publications
1
5
0
3
Order By: Relevance
“…Bacterial strains that express SAgs are commonly isolated and are more virulent than nonproducing strains [24]. Approximately 40% of isolates from both healthy carriers and clinical cases are capable of expressing one or more SAg [25,26]. Yet, pathologies that are directly attributable to SAg alone probably occur only under exceptional conditions, despite the likelihood of frequent exposures to toxigenic bacteria.…”
Section: The Superantigen and Disease Paradigmmentioning
confidence: 99%
“…Bacterial strains that express SAgs are commonly isolated and are more virulent than nonproducing strains [24]. Approximately 40% of isolates from both healthy carriers and clinical cases are capable of expressing one or more SAg [25,26]. Yet, pathologies that are directly attributable to SAg alone probably occur only under exceptional conditions, despite the likelihood of frequent exposures to toxigenic bacteria.…”
Section: The Superantigen and Disease Paradigmmentioning
confidence: 99%
“…However, studies of patients with SAB found similar distributions of enterotoxins (SEA to SEG, SEH, SEI, and TSST-1) in strains isolated from patients who did survive and those who did not survive (48,55,241). Furthermore, a prospective study by Desachy et al found no significant difference (OR, 1.60; 95% CI, 0.34 to 7.59; P ϭ 0.55) between the numbers of enterotoxin-producing strains isolated from surviving (70%; 16/23) and deceased (79%; 11/14) community-onset MSSA-B patients (48).…”
Section: Exotoxinsmentioning
confidence: 99%
“…Verschiedene Studien konnten zeigen, daß zwischen 25%-40% der untersuchten 5. az/7-<?2<,y-Isolate mindestens eines der drei Superantigene-TSST-1, Enterotoxin B oder Enterotoxin C bildeten [11][12][13][14][15][16][17][18]. Damit wird deutlich, daß immerhin jedes vierte S. aureus-Isolat unter bestimmten Bedingungen über eine Superantigenbildung ein TSS auslösen könnte.…”
Section: Diskussionunclassified
“…Dies wiederum impliziert, daß es neben Superantigenen auch alternative Ursachen bzw. Mechanismen für einen grampositiven Schock geben muß [11][12][13][14][15][16][17][18].…”
unclassified